The Urgency of Women's Involvement in the Decision-Making Process of Resolving Cases of Violence Against Women - Rabbany, Najmi Mumtaza (Devotion : Journal of Research and Community Service, 2022)
Violence against women is currently rife in Indonesia. This incident did not only occur in one or two areas, but occurred in various regions and in various forms. One form of violence against women is mass rape or what is familiarly called gang rape. Where this term refers to a rape of women carried out in groups. The state in this case should have a role through the existing state institutions. The role of community groups is also important in dealing with cases of violence against women. The theory of the importance of women's involvement in the decision-making process put forward by Chusnul Mar'iyah and other feminist theories will be the analytical knife of this research in understanding the involvement of the state and groups in society facing cases of violence against women, especially gang rape.